Avaliação experimental da atividade antidiarréica do látex do croton urucurana baill - Gurgel, Luilma Albuquerque (2000)
The red sap (Dragon’s Blood ou Sangre de Grado) extracted from some Croton species is used in folk medicine for the treatment of cancer, rheumatism, wounds, ulcers, diarrhoea and to combat infections. The aim of this study is to evaluate a possible antidiarrhoeic activity of the sap extracted from Croton urucurana Baill. (SCU) and to elucidate the possible mechanism involved on this activity, explaining and justifying the popular use of this plant for the treatment of diarrhoea. The experimental models used were, castor oil-induced diarrhoea in rats and mice, gastrointestinal transit and cholera toxin-induced intestinal secretion in mice, and contractile responses evoked by agonists (acetylcholine, barium chloride and 5-HT) in isolated rat jejunum. SCU (400, 600 and 800 mg/kg, p.o.) produced a significant antidiarrhoeic activity. However, in the castor oil-induced diarrhoea model, in rats, neither L-arginine (600 mg/kg, i.p.) nor naloxone (2 mg/kg, s.c.) reverted the SCU (800 mg/kg, p.o.) antidiarrhoeic activity. On the gastrointestinal transit SCU produced a significant (p<0,01) inhibitory effect at all the test doses employed. However, naloxone (2 mg/kg, s.c.), L-arginine (600 mg/kg, i.p.) and ioimbine (1 mg/kg, i.p.) failed to mitigate in a significant manner, this inhibitory effect of SCU. When tested on physostigmine-induced gastrointestinal transit, SCU (600 mg/kg, p.o.) showed no significant inhibition indicating absence of anticholinergic action. The cholera toxin-induced intestinal secretion was inhibited by SCU (600 mg/kg, p.o.) and this inhibition was greater than that observed with chlorpromazine (25 mg/kg, p.o.), an established antisecretory drug. In isolated rat jejunum, SCU markedly inhibited the contractile responses evoked by 5-HT, but failed to modify the contractile responses of other two agonists, barium chloride and acetylcholine. SCU showed low toxicity, the LD50 (letal dose for 50% of the animals) registered was 5,20 +/- 0,13 g/Kg, per oral route. In conclusion, the results of this study suggest that the sap extracted from Croton urucurana presents antidiarrhoeic activity, confirming its popular use, and can be explored as an alternative treatment for diarrhoea, alone or in combination with the oral rehydration solution. Though, its mechanism of action is unclear, but its effect is independent of opioid, cholinergic, alpha2-adrenergic or nitriergic mechanism.